Role of protein tyrosine phosphatase 1B (PTP1B) in the increased sensitivity of endothelial cells to a promigratory effect of erythropoietin in an inflammatory environment - Chamorro, María Eugenia (2020)
The proliferation and migration of endothelial cells are vascular events of inflammation, a process which can also potentiate the effects of promigratory factors. With the aim of investigating possible modifications in the activity of erythropoietin (Epo) in an inflammatory environment, we found that Epo at a non-promigratory concentration was capable of stimulating EA.hy926 endothelial cell migration when TNF-α was present. VCAM-1 and ICAM-1 expression, as well as adhesion of monocytic THP-1 cells to endothelial layers were also increased. Structurally modified Epo (carbamylation or N-homocysteinylation) did not exhibit these effects. The sensitizing effect of TNF-α on Epo activity was mediated by the Epo receptor. Inhibition assays targeting the PI3K/mTOR/NF-κB pathway, shared by Epo and TNF-α, show a cross-talk between both cytokines. As observed in assays using antioxidants, cell migration elicited by TNF-α + Epo depended on TNF-α-generated reactive oxygen species (ROS). ROS-mediated inactivation of protein tyrosine phosphatase 1B (PTP1B), involved in Epo signaling termination, could explain the synergistic effect of these cytokines. Our results suggest that ROS generated by inflammation inactivate PTP1B, causing the Epo signal to last longer. This mechanism, along with the cross-talk between both cytokines, could explain the sensitizing action of TNF-α on the migratory effect of Epo.